Penerimaan Dispensasi Kawin di Pengadilan Agama Kepahiang Kelas II Perspektif Maqashid Syariah - Ibdaria Oktavianti; Ismail Jalili; Sirajuddin M (Journal of Sharia and Legal Science, 2023)
This study discusses what factors are used as reasons for requesting a marriage dispensation at the Kepahiang Religious Court, the legal basis that the judge considers in granting the marriage dispensation and maqashid sharia review of the marriage dispensation at the Kepahiang Religious Court. This type of research is a type of field research using a qualitative descriptive approach. The research data was taken directly from the research location and the data was obtained using interview, observation and documentation methods. After the data has been collected to analyze the data collected in this study, descriptive-analytic analytical techniques are used, namely to describe all the things that are the focus of this research. The results of the study areThe reasons for the dispensation of marriage are:pregnant out of wedlock, already had intercourse (adultery) and worried about adultery. The legal basis used by the judge is:(UU) of the Republic of Indonesia Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage,Compilation of Islamic Law and Perma Number 5 of 2019 concerning Guidelines for Adjudicating Applications for Dispensation of Marriage. Meanwhile, the judge's consideration apart from containing juridical aspects must also be considered sociological and psychological aspects to realize benefit. As for the review of Maqashid Syariah, this is part ofhifzh nasl (maintaining offspring) where this principle emphasizes the principle of the best interests of the child because the person applying for the dispensation of marriage is still underage and it is feared that it will have an impact on their offspring.